Students’ Perception of the Enforcement Model Approach Towards Radicalism Movement in Malaysia Higher Learning Institutions (HLI’s) - Ismail, Alice Sabrina; Muhammad Mujtaba Habibi; Azalilah Ramdani Musa; Shahariah Norain Shaharuddin (Advances in Humanities and Contemporary Studies, 2023)
Radicalism among undergraduates in a higher learning institution (is an HLI’s) thing that is already synonymous in most countries of the world, especially in developing nations. The radicalism brought about by the student movement is not triggered, but it is often influenced by the issue of statehood which is a factor in social change and the formation of community values. The student body movement has enormous potential to influence and shape the country’s political landscape as it also indirectly acts as most people’s voice. However, the involvement of students in higher learning institutions (HLI’s) in Malaysia is now not as intense and aggressive as in the foreign context. Based on scientific studies, student participation in Malaysia is deficient and deteriorating through their involvement in partisan politics, especially in the early 20th century. In other words, the students lack awareness and concern about the current political issues and problems around them. The function of students once upon a time as community spokespeople are now eroding in Malaysia. Now, students are no longer agents of change, not anymore voicing public groans, and not thus far sensitive to issues outside the campus. The enforcement of the University College University Act (AUKU) 1971 in Malaysia, which prohibits students from engaging in politics for five decades, has caused some passivity and paralysis in the students’ interest in political activities. Therefore, this study focuses on three (3) primary objectives. First, to identify the development of radicalism among students in three HLI’s in Malaysia. Second, to analyze the Student’s perception and satisfaction with the enforcement model of the University College University Act (AUKU) 1971. Thirdly, is to develop a resilience model in preventing radicalism in a more student-friendly scenario that does not constrain students’ rights in Malaysia, like the Universities and University Colleges Act (AUKU), by benchmarking the good practices in Indonesia’s Higher Learning Institution (HLI’s) using the Altbach’s theoretical framework. Thus, this study uses quantitative methods to analyze the questionnaire accurately. Three HLI’s – UTM, UKM and UM are involved in this study and selected according to the required elements. The findings showed that the reliability value of the study instrument was α = 0.906. The questionnaire data were analyzed using the Statistical Package for Social Sciences (SPSS) software version 20.0. The study found that students’ perception of the AUKU enforcement model was poorly satisfactory and required a review. Although the enforcement of AUKU aimed at ensuring harmony in creating a conducive campus learning environment, its more worrying adverse effects must be overcome as universities function not to be controlled factories but also as repositories and generators of knowledge for producing great and intellectual national leaders regardless of their calibre and performance.